Effectiveness of safety programs in Malaysian construction industry - Attau, Jaimey (2014)
Construction accident rate in Malaysia had increased tremendously. This research was to investigate proactive indicator in construction industry and to propose improvement of implementation of the safety programs. Comprehensive literature review has been carried out to gather the information on the essential safety programs and the proactive safety performance indicator in construction industry. This was followed by a structure questionnaire, distributed to the selected project team player, as a main tool to gain data to explore the level of effectiveness and implementation of safety programs and the proactive safety performance indicator in Malaysian construction industry. The data collected has been analysed by using Relative Index technique. Twenty one (21) essential safety programs and thirty nine (39) sub element proactive safety performance indicators were identified. From the research, the site safety performance is very much influenced by the implemented safety programs such as implementation of safety inspection and safety induction